The Sacred Function of Natural Colors in Geringsing Fabric Amidst the Pegringsingan Ceremony - I Made Rai Artha; A.A Putu Mediastari; Ida Bagus Wiryanatha (Blantika: Multidisciplinary Journal, 2026)
This study examines the sacred function of natural colors in Geringsing weaving within the cultural and spiritual life of the Tenganan Pegringsingan community in Bali. Geringsing cloth is a traditional double ikat textile that holds deep symbolic, ritual, and philosophical meanings for the Balinese Aga people. The use of natural dyes derived from plants such as noni roots, candlenut oil, and indigo leaves reflects the local wisdom and cosmological beliefs related to harmony between humans, nature, and spiritual forces. The purpose of this research is to analyze the sacred meanings of natural colors, the procedures for selecting natural dye materials, and the implications of Geringsing weaving for the local community. This study employed a descriptive qualitative method with a cultural and interpretive approach. Data were collected through observation, in-depth interviews, documentation, and triangulation involving traditional leaders, weavers, and local community members in Tenganan Pegringsingan Village. The findings reveal that the tridatu colors red, black, and white or beige symbolize cosmic balance, spiritual protection, and holistic well-being. The process of dye selection and weaving is closely connected to rituals, customary rules, and beliefs inherited across generations. In conclusion, Geringsing weaving is not merely a textile product but also a sacred cultural heritage that integrates spirituality, identity, ecological awareness, and traditional values within the life of the Tenganan Pegringsingan community